Confined Ru Nanocatalysts on Surface to Enhance Ammonia Synthesis: An In situ ETEM Study. Issue 2 (18th November 2020) - Ding, Jia; Wang, Lizhuo; Wu, Ping; Li, Ang; Li, Wei; Stampfl, Catherine; Liao, Xiaozhou; Haynes, Brian S.; Han, Xiaodong; Huang, Jun
Abstract: Ammonia is an important feedstock for producing fertilizer and chemicals as well as is also a potential energy carrier. Generally, MgO is considered as an electronic promoter for Ru catalysts in ammonia synthesis. In this research, it was found for the first time that surface atoms of Ru particles are stabilized by MgO modification at high temperature and reaction atmosphere, which contained more highly active B5‐sites for ammonia synthesis. Ex situ HRTEM images show similar Ru nanoparticles containing steps with or without promoters. Under reaction temperatures and gas environment, in situ environmental transmission electron microscopy (ETEM) observe that Ru particles without MgO promoter suffer from dynamic change and lost the B5‐sites on Ru steps, which results in the poor ammonia yield obtained by both the continuing‐flow reaction system. While MgO modification can stabilize the Ru surface structure and keep B5‐sites there, which contributes to the much higher ammonia yield. Density functional theory calculations show that B5‐site is a catalytic active center for ammonia synthesis and the N2 dissociation barrier on B5‐site containing step is lower than B5‐site‐free step on Ru nanoparticles. The finding provides a new explanation for the high activity of MgO modified Ru catalysts. Moreover, adding CsOx with MgO will contribute electron donation to stabilized Ru surface and accelerate the ammonia synthesis with five‐fold higher than MgO−Ru/MS at 500 °C. A better fundamental understanding of the dynamics of Ru catalysts and its reaction mechanism in this research is vital for optimizing the design of catalysts for ammonia synthesis. Abstract : By In situ environmental transmission electron microscopy (ETEM), it was observed that Ru particles without MgO promoter suffer from dynamic change and lost the B5‐sties on Ru steps in H2 /N2 gaseous atmosphere, associated with poor ammonia yield. While MgO doping can stabilize the Ru surface structure and keep more B5‐sites, resulting in higher ammonia synthesis activity.